Green synthesis of titanium dioxide nanoparticles using Phyllanthus niruri leaf extract and study on its structural, optical and morphological properties. (2020) - Shanavas, S.; Priyadharsan, A.; Karthikeyan, S.; Dharmaboopathi, K.; Ragavan, I.; Vidya, C.; Acevedo, R.; Anbarasana, P.M.
Abstract: In this research non-toxic, cost-effective TiO2 nanoparticles were prepared using Phyllanthus niruri leaf extract. The crystallinity and purity of green treated TiO2 nanoparticles were investigated using X-ray diffraction (XRD) studies. The specific functional groups responsible for the reduction of TiO2 nanoparticles were analyzed using Fourier transform infrared spectroscopy (FTIR). The formation of spherical shaped TiO2 nanoparticles was confirmed using Transmission electron microscopy (TEM). The optical properties of green treated TiO2 nanoparticles reveled through UV–Vis-Diffused reflectance spectroscopy (DRS). The obtained results show that the green treated TiO2 nanoparticles can act as a better photocatalytic material.